Psychometric Assessment of Shortened Mental Toughness Questionnaires (MTQ): Factor Structure of the MTQ-18 and the MTQ-10 - Dagnall, Neil; Denovan, Andrew; Papageorgiou, Kostas A.; Clough, Peter Joseph; Parker, Andrew; Drinkwater, Kenneth Graham (Frontiers in Psychology, 2019)
The 18-item Mental Toughness Questionnaire (MTQ-18) is a brief, widely used measure of mental toughness. The MTQ-18 derives from the longer MTQ-48, which comprises four independent but correlated factors (Challenge, Commitment, Control and Confidence). Despite sampling items from across MTQ-48 dimensions, the MTQ-18 (as intended) provides a global, unidimensional score. Researchers have recently developed a further abridged version of the MTQ-18, the MTQ-10, which has demonstrated promising psychometric performance. The current paper assessed the factorial structure, reliability, predictive validity and invariance of the MTQ-18 and MTQ-10 in a sample of 944 students from English independent schools (year 11, aged 16 years). Respondents completed the MTQ-18 items online alongside the Satisfaction with Life Scale. Confirmatory factor analysis revealed that the MTQ-10 was a superior general measure, because the MTQ-18 possessed additional variance to that accounted for by a unidimensional solution. Additionally, the MTQ-10 evidenced higher factor loadings and demonstrated better data-model fit. Tests of concurrent validity revealed the MTQ-10 was a stronger predictor of well-being (life satisfaction). Both the MTQ-18 and MTQ-10 demonstrated gender invariance at the configural, metric and scalar level. Overall, although the MTQ-18 was a psychometrically acceptable measure, the MTQ-10 was a superior unidimensional measure of MT.